2014
DOI: 10.1039/c4pp00005f
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical and microbial alterations of DOM spectroscopic properties in the estuarine system Ria de Aveiro

Abstract: The influence of photochemical transformations of chromophoric dissolved organic matter (CDOM) on microbial communities was evaluated in the estuarine system Ria de Aveiro. Two sites, representative of the marine and brackish water zones of the estuary, were surveyed regularly in order to determine seasonal and vertical profiles of variation of CDOM properties. Optical parameters of CDOM indicative of aromaticity and molecular weight were used to establish CDOM sources, and microbial abundance and activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…Comparable trends have been found by Zhang et al (2007b) in the Yunnan Plateau lakes. E2 : E3 ratio variations found in this study have also been shown in previous studies (Santos et al, 2014;Helms, 1998). In coastal waters E2 : E3 values are typically within the range 8.70±1.4 and 13.5±1.6 (nearshore -offshore in Georgia Bight; Helms et al, 2008).…”
Section: Dynamics Of Dissolved Organic Carbonsupporting
confidence: 92%
“…Comparable trends have been found by Zhang et al (2007b) in the Yunnan Plateau lakes. E2 : E3 ratio variations found in this study have also been shown in previous studies (Santos et al, 2014;Helms, 1998). In coastal waters E2 : E3 values are typically within the range 8.70±1.4 and 13.5±1.6 (nearshore -offshore in Georgia Bight; Helms et al, 2008).…”
Section: Dynamics Of Dissolved Organic Carbonsupporting
confidence: 92%
“…These patterns are consistent with depletion processes taking place in the SML environment through the photochemical processing of organic material. Negative correlations between the SML HIX and exposure to solar radiation have been reported by Santos et al (2014), and associated with a low content of fluorophore groups corresponding to humic-like fractions . Our observations are consistent with the loss of fluorescent intensity from FDOM compounds due to photochemical degradation in the SML.…”
Section: Influence Of Solar Radiation On Hixmentioning
confidence: 79%
“…FDOM decomposition due to interaction with solar radiation is known as photobleaching, a process that provides a source of smaller compounds increasing the availability of carbon substrates in the ocean (Santos et al, 2014). Besides photochemical decomposition, high exposure to solar radiation, specifically to the more energetic wavelengths of ultraviolet (UV) radiation, leads to the growth of unique microbial communities with specific survival strategies for the harsh environment of the SML; e.g., the release of sun blocker-like compounds (Gao and GarciaPichel, 2011).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…However, photochemical transformations likely represent key degradation pathways for terrestrial DOM in alpine and sub-alpine lakes due to the intensive solar irradiation at higher altitudes (Sommaruga, 2001). The photodegradation of DOM results in the alteration of its molecular structure and mineralization of DOC to CO 2 (Kaiser and Sulzberger, 2004;Piccini et al, 2009;Osburn et al, 2011;Santos et al, 2014). The overall effects of photodegradation, depend largely on the irradiation conditions and the origin and composition of the DOM exposed to sunlight (Stedmon and Markager, 2005b;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%